Use of Internet in school students of Lima Metropolitana - Quezada Zevallos, Jenny (2005)
It´s a report of the research about the use of Internet in school students, in a 149 students boys and girls, 6 to 12 years sold, study 1, 2 or 6 Primary Level, from state and private schools to Lima Metropolitans. The instrument was an survey. The results shows families give importance to get a computer for their sons; also special characteristic in the way to learn the use of Internet, time of use, applications more frequently, the people who atted with the students and others aspects.